3‐D Structure of the Northern Oman‐UAE Ophiolite: Widespread, Short‐Lived, Suprasubduction Zone Magmatism. Issue 1 (22nd January 2019) - Ambrose, Tyler K.; Searle, Michael P.
Abstract: The Oman‐United Arab Emirates (UAE) ophiolite is the most intensely studied ophiolite on Earth, is commonly used as a template for other poorly exposed and structurally complex ophiolites, and is often used as an analog for fast‐spreading mid‐ocean ridges like the East Pacific Rise. Several recent studies, including the largest ever focused on the UAE, have suggested that the pseudostratigraphy of the ophiolite in the UAE is distinct from Oman. Such interpretations have led researchers to propose that the UAE portion of the ophiolite underwent a separate magmatic and tectonic evolution. We present a profile along a new road section in the UAE that reveals continuous exposure of the entire ophiolite section and places key constraints on the internal architecture. We infer the geometry of the ophiolite thrust sheet and propose a model for the structure, pseudostratigraphy, and evolution of the ophiolite in the UAE that is simplified yet more consistent with geochemical and geochronological data. Our results indicate that (1) the architecture of ophiolite in the UAE is similar to Oman, and there is no reason to infer a different tectonic history, (2) the ophiolite is gently folded but largely intact, (3) extension and magmatism during formation of the ophiolite was broadly distributed, (4) there are no large gabbro bodies in the mantle sequence; they are all above the petrological Moho, and (5) the entire magmatic sequence was generated in a short time (~1 million years), and thus, the ophiolite cannot be compared to the long‐lasting (>100 million years) fast‐spreading East Pacific Rise. Plain Language Summary: Ophiolites—slices of oceanic crust and upper mantle that have been thrust onto the continental margin—provide the opportunity to study the structure and genesis of oceanic lithosphere formed. The Oman‐United Arab Emirates (UAE) ophiolite is the largest and most intensely studied on Earth and has been fundamental to our understanding of other ophiolites and oceanic lithosphere in general. Several recent studies have suggested that the northern segment of the Oman‐UAE ophiolite exhibits a different internal structure from the rest of the ophiolite. This has led several researchers to propose that the northern ~20% of the ophiolite underwent a distinct magmatic and tectonic evolution. To test the hypothesis that the architecture of the northern part of the ophiolite is considerably different, we studied a transect across the ophiolite in the UAE that utilized newly exposed road cuts that provide complete 3‐D exposure of the ophiolite. We demonstrate that the apparent differences in internal structure are the result of a nearly horizontal and undulating Moho transition zone and complex magmatic relationships. We conclude that the architecture of northern section of the ophiolite is not considerably different from further south. Thus, there is no evidence to support a distinct tectonic and magmatic evolution. Key Points: The architecture of ophiolite in the UAE is similar to Oman, and there is no reason to infer a different tectonic history Extension and magmatism during ophiolite formation were broadly distributed, rather than localized along a single ridge axis The ophiolite sequence is gently folded but largely intact There are no large gabbro bodies in the mantle sequence; they are all above the petrological Moho